(3eKjQ GdZQGe Edi RjGQI GdbOS hGdTGes - (3CHh eMeO eMehO Hf ESeGYjd Hf eMehOs ((3eMeO Hf YeQ Hf YHO GdQMef s)
(3ChdgG (B:s
(3GdMeO ddg GdPi RGO eSLOfG GdCbUi TQakG HGdESQGA Edjg HNjQ GdHTQ CeG HYO agPG cJGH faGFS GdNWQ Ldjd GdbOQ SejJg eKjQ GdZQGe Edi RjGQI GdbOS hGdTGe hLYdJ GdcJGH Ydi bSejf GdbSe GdChd ai aVd GdTGe hHjGf MOhOg s
(3BNQgG (B:s
(3bGd CHh eMehO YaG Gddg Yfg Ef GdbOS GdTQja HdO YXje CLeYJ GdWhGFa Ydi JYXjeg NdG GdWGFaI GdSGeQg aEfge jbhdhg Ef GdbOS GdTQja LHd fGHdS hNGdahG LejY GdCee ai Pdc hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI (B- (3HGQjS s
Keywords: (3GdJGQjNs